A Validated Questionnaire to Assess the Severity of Persistent Postural-Perceptual Dizziness (PPPD): The Niigata PPPD Questionnaire (NPQ). Issue 7 (August 2019) - Yagi, Chihiro; Morita, Yuka; Kitazawa, Meiko; Nonomura, Yoriko; Yamagishi, Tatsuya; Ohshima, Shinsuke; Izumi, Shuji; Takahashi, Kuniyuki; Horii, Arata
Abstract : Objective: To establish a questionnaire to diagnose and assess the severity of persistent postural-perceptual dizziness (PPPD). Study Design: Retrospective chart review. Setting: Tertiary referral center. Patients: Fifty PPPD patients and 50 consecutive control patients with other vestibular disorders. Interventions: Patients answered questions on three exacerbating factors of PPPD (upright posture/walking, movement, and visual stimulation), and each factor was evaluated using four questions scoring the severity from 0 (none) to 6 (unbearable). Somatic and psychological distress was evaluated by the Visual Analog Scale (VAS) and the Hospital Anxiety and Depression Scale (HADS), respectively. Main Outcome Measures: The questionnaire's reliability was tested by Cronbach's alpha, and it was validated by examining the differences in the questionnaire's scores between PPPD patients and controls. The area under the curve (AUC) of the receiver operating characteristic curve for each factor was calculated. Results: Cronbach's alpha coefficient was >0.8 for all factors, except the movement factor. There were no significant differences in the VAS and HADS scores between the two groups. However, the combined and individual questionnaire scores for each factor were higher in PPPD patients than in controls, indicating the questionnaire's high validity. The AUC was widest for the visual stimulation factor (0.830), and a score of 9 (full score 24) had the best sensitivity (82%) and specificity (74%) for discriminating PPPD patients from controls. Conclusions: We developed a questionnaire that exhibited high reliability and validity in evaluating PPPD severity. The visual stimulation factor may be the most characteristic among the three exacerbating factors.